Lexical features of anthroponyms related to the vocabulary of household items - Mashhura Abdujalilova (Goodwood Publishing, 2025)
Purpose: This study aims to explore the lexical features of anthroponyms, focusing on their relationship with household vocabulary and their significance within the broader linguistic system. By examining how personal names are formed, used, and adapted across cultures, the research highlights their semantic, cultural, and pragmatic roles in society. Research methodology: The research applies a descriptive linguistic approach, analyzing theoretical perspectives from Uzbek and English onomastic scholarship. Comparative analysis of anthroponymic systems is conducted using linguistic, ethnographic, and pragmatic frameworks to reveal both universal and culturally specific naming practices. Results: Findings indicate that anthroponyms, beyond their primary naming function, encapsulate historical, cultural, and linguistic information. The study shows that naming customs reflect socio-economic conditions, spiritual beliefs, and cultural integration. Comparative insights reveal similarities in the role of names as markers of identity, while highlighting differences in legal regulation and cultural traditions between Uzbek and English contexts. Conclusions: The research concludes that anthroponyms are not merely identifiers but integral components of cultural identity and social interaction. Their analysis provides deeper understanding of the dynamics between language, culture, and society. Limitations: The study is primarily theoretical and descriptive, with limited empirical data. Broader cross-linguistic and ethnographic studies would strengthen the findings. Contribution: This work contributes to the fields of lexicology, onomastics, and linguopragmatics by emphasizing the role of anthroponyms as cultural and linguistic units that bridge personal identity and collective heritage.